Oasenwirtschaft in den Maghrebländern: Zur Revision des Forschungsstandes in der Bundesrepublik - Popp, Herbert (ERDKUNDE, 1990)
In this research report the author first refers to the opinion widespread in German geography, that the oases of the Maghrib are characterized by an economic decline. The main purpose of the contribution is to call into question this opinion. This is done on the one hand through the presentation of new social-geographic results the author arrived at in the East Moroccan oasis of Figuig, on the other hand by referring to a lot of further books and articles published recently on other oases in the Maghrib. All these contributions show that within traditional oases numerous innovative processes take place - and that consequently the thesis that the oases are dying is wrong. Arguments are collected in order to explain why such a one-sided image of the oasis could come into existence in German geography. In connection with this it is shown a) that this negative view of the oases is not borrowed from the French research work on oases, b) that numerous publications are only based on short and superficial travels and that thus misjudgements resulted from the fact that too much emphasis was laid on physiognomic impressions in the oases, and c) that the oases, where a lot of research work has been carried out and to which the authors refer, are not typical for the Maghrib countries as a whole. The contribution concludes with a plea for a future social-geographic research on oases. This is to be done in cooperation with native researchers of the Maghrib countries and with a stronger emphasis on applicable aspects.